A Validated Stability Indicating RP-HPLC Method Development for Platelet Aggregation Inhibitor Ticagrelor in Bulk and Tablet Formulation - Kirtimaya Mishra (Journal of Global Pharma Technology, 2019)
A stability-indicating Reverse Phase-HPLC technique for the quantification of Ticagrelor (TCG) in pharmaceuticals was developed and validated. Chromatography was done on Phenomenex Luna C18 5μm (250 mm×4.6 mm) analytical column with acetonitrile: methanol: water in 40:30:30% v/v/v ratio as mobile phase and 0.9 ml/min as a flow rate. TCG was detected at 280 nm UV-wavelength maximum. In this present research work developed technique was validated over 20-150μg/ml linear concentration range for TCG. This method was accepted with linearity coefficient value of 0.99 and the percentage recovery was found to be 99.3%. This method was shown with LOD and LOQ findings of 0.53μg/ml and 1.61μg/ml respectively. The drug was degraded in acid and alkaline medium and the percentage degradation values were 3.10 % and 4.54 % respectively. There was no degradation of drug when wide open to neutral, UV, thermal, sun-light and oxidative conditions. Drug was undergoing degradation when exposed to acid and alkaline conditions.Keywords: Ticagrelor, Reproducible, Degradation, Oxidative conditions.